(untitled) (Revista de História Regional, 2007)
This work talking about the Concretism, movement that emerge in the Brazil in an age that artists and intellectuals make their production the propagation of freedom politics-revolutionaries, linked at the development and modernization of the Brazilian society. The wider purpose is to understand the kind of relations that linked poetry, politics and History.